ANALISIS TARGET DAN REALISASI PENERIMAAN PAJAK DAERAH NUSA TENGGARA BARAT - Siti Yulianah M. Yusuf; Basuki Sri Hermanto; Iswan Iswan (Bajang Institute, 2026)
Local tax revenue is a primary source of Locally-Generated Revenue (PAD), collected based on local regulations and national laws, such as Law Number 1 of 2022. These funds are crucial for financing regional expenditures, enhancing fiscal independence, and supporting public welfare through infrastructure development and public services. Local taxes differ from user fees, while fees provide direct benefits to the payer such as parking or market fees taxes are utilized for general funding purposes.This study employs a qualitative research method. The findings indicate that the setting of tax targets takes into account regional revenue growth rates, macroeconomic indicators, and policies regarding the intensification and extensification of local taxes. Tax revenue targets in West Nusa Tenggara (NTB) Province have shown fluctuating annual increases. While the realized revenue for certain types of local taxes has met the targets, others have fallen short. However, during the 2023–2025 period, shortfalls in specific tax categories were offset by the performance of other taxes that exceeded their targets, resulting in the overall local tax revenue target being surpassed.